Methodology for the Regulation of Over-the-top (OTT) Services: The Need of A Multi-dimensional Perspective - Tekin Bilbil, Ebru (International Journal of Economics and Financial Issues, 2018)
Over the past decade, the contemporary literature has addressed the emerging factors influencing the new economy of over-the-Internet and Over-The-Top (OTT). The growth of the OTT market conveyed the need for the discussion on the best possible and most appropriate regulatory approach that should be undertaken. This study emphasizes the importance of a multi-dimensional outlook for OTT regulation in order to uncover different types of OTT services. This outlook includes the diverse forms of relationship between new and current influential factors (i.e., market model, business impact, infrastructure requirements) and area of regulation. This paper describes a balanced regulatory framework based on a cooperative approach that is more effective for OTTs. Similarly, the OTT regulation has not been included in the regulatory agenda in Turkey due to low penetration rates and cooperative approach between OTT service providers and telco companies. As a result, this work proposes a multi-dimensional methodology for this emerging new area that requires regulation. Keywords: OTT, Services, Regulation, market, network, policy, competition, telecommunications, internet JEL Classifications: G28, L86, L96 https://doi.org/10.32479/ijefi.5809